Acetyl-CoA Carboxylase Alpha Gene Polymorphism and Its Association with Milk Fatty Acid of Holstein Friesian Using Real-Time PCR Method - R. Azis; Jakaria; A. Anggraeni; A. Gunawan (Tropical Animal Science Journal, 2020)
Milk fatty acids are largely affected by genetic factors. Acetyl-CoA Carboxylase Alpha (ACACA) gene is one of the important genes in regulation and metabolic function of milk fatty acids in dairy cattle. The objective of this study was to find out the relationship of single nucleotide polymorphism (SNP) ACACA gene with milk fatty acid trait in local dairy cattle. A total of 277 samples of Holstein Friesian (HF) were collected from Indonesian Research Institute for Animal Production (IRIAP), Animal Breeding Center and Forage Feed of Baturraden (ABCFFB), Central Java Province, Animal Husbandry Training Center of Cikole (AHTCC), West Java Province, Singosari Artificial Insemination Station (Singosari AIS), East Java Province, and Lembang Artificial Insemination (Lembang AIS), West Java Province, Indonesia. Genotyping of this SNP marker (g.2203G>T) was analyzed using the real-time Polymerase Chain Reaction (PCR) based on the hybridization TaqMan probe as the method for allelic discrimination. Milk samples were analyzed using Gas Chromatography and Mass Spectrometry (GCMS). The results of this study revealed the GG and GT genotypes. The proportion of the GG genotype frequency (0.88) was higher than the GT genotype (0.11) and the G Allele frequency was shown higher than the T allele in all locations, i.e., 0.942 and 0.08, respectively. The ACACA gene g.2203G>T SNP was significant (p<0.05) for lauric (C12:0) and dodecanoic (C17:1) acids. It was concluded that the ACACA gene g.2203G>T SNP could be useful as a marker selection for milk fatty acid such as lauric and dodecanoic fatty acids.